2015
DOI: 10.1159/000439198
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Features of Vulvar Lichen Sclerosus in the Setting of a Prospective Cohort of Patients: New Observations

Abstract: Objective: Dermoscopic features of vulvar lichen sclerosus (VLS) were investigated in order to determine both vascular and non-vascular features of this disease. Materials and Methods: Dermoscopic images of 35 patients affected with histopathologically confirmed VLS were evaluated for the presence of predefined morphological criteria. Results: On dermoscopy, VLS lesions exhibited very sparse vessels, mainly linear, without a specific arrangement. Dotted vessels were observed mostly in the early stage of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Structures like ice slivers, presenting linear or triangular or lanceolated shape, were observed inside the whitish areas in four patients. On the basis of our previous study, their histological correspondence is not clear . These dermoscopic features were less observable after treatment, although without significant difference in mean scores.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Structures like ice slivers, presenting linear or triangular or lanceolated shape, were observed inside the whitish areas in four patients. On the basis of our previous study, their histological correspondence is not clear . These dermoscopic features were less observable after treatment, although without significant difference in mean scores.…”
Section: Discussionmentioning
confidence: 65%
“…On the contrary, gray-blue dots, arranged in a typical peppering pattern, did not change in a significant way after treatment compared with baseline. In a previous study, we found that gray-blue peppering corresponds to melanophages displaced in the upper dermis and at perifollicular site, as a consequence of the inflammatory process, 7 and is observable also in lichen planus. 10 Based on our findings, peppering is not affected by the application of corticosteroids.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Considering the dermoscopic variables addressed in this analysis in detail, mean vessel scores significantly increased after treatment in the whole population as well as in each treatment group. On the contrary, mean scores of both patchy, structure‐less, whitish areas and whitish background, which represent two dermoscopic hallmarks of VLS (Borghi et al, , Dermatology; Larre Borges et al, ), had decreased significantly at treatment completion when compared with baseline (Figure ). All together, these relevant dermoscopic changes probably reflect the decrease of dermal hyalinization and sclerosis induced by corticosteroid treatment (Dalziel et al, ), as previously hypothesized.…”
Section: Discussionmentioning
confidence: 97%